Energy-efficient inland cargo ship design based on fuel consumption and CO2 emission control using CFD - Hasan, S M Rashidul; Karim, Md Mashud (Journal of Naval Architecture and Marine Engineering, 2023)
Inland ships usually face some additional restrictions in comparison to the sea-going ship. Apart from the regulations imposed by each country, the effect of restricted waterways governs the major ship design constraints. For this reason, designing energy-efficient inland ships incorporating shallow water effects is very challenging. There is little research done to overcome these challenges; most of them lack the comparison of improved design with the existing one. This paper has analysed1634 general cargo ships from existing Bangladeshi inland cargo ships' data and considered 281 ships only for performance evaluation after data verification. The selected cargo ships were further assessed by using revised Energy Efficiency Design Index (EEDI) parameters applicable for inland ships of Bangladesh. Fuel efficient and less CO2 emitter efficient cargo ships were identified. After considering the effect of shallow water, a set of ship design suggestions is proposed. These suggestions were validated by redesigning an existing cargo ship based on the suggestions and comparing their resistance with the parent hulls. Computational Fluid Dynamics (CFD) is used to calculate the ship resistances and it is found that 13%reduction in total resistance can be achieved simply by choosing improved principal particulars based on the proposed design suggestions. J. Nav. Arch. Mar. Engg., Vol 20(2), December, 2023; p 1-10